Biocompatibility of bio based calcium carbonate nanocrystals aragonite polymorph on NIH 3T3 fibroblast cell line - Abdullahi, Shafiu Kamba; Ismail, Maznah; Tengku Ibrahim, Tengku Azmi; Abu Bakar @ Zakaria, Md Zuki (African Traditional, Herbal Medicine Supporters Initiative, 2014)
Background: Currently, there has been extensive research interest for inorganic nanocrystals such as calcium phosphate, iron oxide, silicone, carbon nanotube and layered double hydroxide as a drug delivery system especially in cancer therapy. However, toxicological screening of such particles is paramount importance before use as delivery carrier. In this study we examine the biocompatibility of CaCO3 nanocrystal on NIH 3T3 cell line. Material and Methods: Transmission and field emission scanning electron microscopy (TEM and FESEM) were used for the characterisation of CaCO3 nanocrystals. Cytotoxicity and genotoxic effect of calcium carbonate nanocrystals in cultured mouse embryonic fibroblast NIH 3T3 cell line using various bioassays including MTT, and Neutral red/Trypan blue double-staining assays. LDH, BrdU and reactive oxygen species were used for toxicity analysis. Cellular morphology was examined by scanning electron microscopy (SEM) and confocal fluorescence microscope. Results: The outcome of the analyses revealed a clear rod-shaped aragonite polymorph of calcium carbonate nanocrystal. The analysed cytotoxic and genotoxicity of CaCO3 nanocrystal on NIH 3T3 cells using different bioassays revealed no significance differences as compared to control. A slight decrease in cell viability was noticed when the cells were exposed to higher concentrations of 200 to 400 µg/ml, while increase in ROS generation and LDH released at 200 and 400 µg/ml was observed. Conclusions: The study has shown that CaCO3 nanocrystal is biocompatible and non toxic to NIH 3T3 fibroblast cells. The analysed results offer a promising potential of CaCO3 nanocrystal for the development of intracellular drugs, genes and other macromolecule delivery systems.